Training on the Use of Management Information Systems for Improving the Quality of Service Document - Tarigan, Azhari Akmal; Syafira, Dinda; Padillah, Fahmil (Universitas Islam Negeri Sumatera Utara, 2023)
The essence of government in an area is to provide assistance to the surrounding environment, basically public authority is